Sauna-induced body mass loss in physically inactive young women and men - Podstawski Robert; Boraczyński Tomasz; Boraczyński Michał; Choszcz Dariusz; Mańkowski Stefan; Markowski Piotr (Sciendo, 2016)
Study aim: The aim of this study was to evaluate the relationship between basic somatic features (body mass and height) and body mass loss in physically inactive young women and men exposed to thermal stress in a dry sauna.